Influence of Variation in Hind Leg Structure of Auchenorrhyncha on Their Jumping Performance - Yifei Xu; Christopher H. Dietrich; Wu Dai (Biology)
Four species representing four different families of the hemipteran insect suborder Auchenorrhyncha, Lepyronia coleoptrata (Aphrophoridae), Euricania ocellus (Ricaniidae), Kolla sp. (Cicadellidae) and Tricentrus sp. (Membracidae) were investigated using high-speed photography and scanning electron microscopy to identify hind leg structures that may influence jumping performance. The coxa–trochanteral joint, femur and tibia were found to have distinct structural adaptations that vary among these jumping insects. Froghoppers and planthoppers possess a coxal protrusion which is absent in leafhoppers and treehoppers, the latter featuring a more recessed coxal fossa. The medial coxae of these insects exhibit fields of microtrichia that vary in density and fine structure. Medial gears on the trochanters of Tricentrus sp. are implicated in the storage of energy prior to their jumps. These structural differences manifest in the insects’ jumping performance. The study demonstrated a correlation between the robustness of the microtrichia field interaction and the insect’s jumping capability. Specifically, leafhoppers, equipped with a pair of rivet-like structures connecting the hind coxae, were observed to achieve quicker and more stable take-offs. The study reveals that structural variations in the hind legs of Auchenorrhyncha species significantly influence their jumping performance, with implications for both efficiency and stability.